Challenges Faced by Technical Communication Educators in the Field of ICT- A Systemic Study - Subramanian, Lakshmi (Integrated Journal for Research in Arts and Humanities, 2022)
The article examines ways and means of using computers in technical communication classrooms, including the ways in which we address literacy and humanistic issues through our current instruction. Over the next decade and through the next century, we will face three pedagogical challenges as we use computer technology to support our teaching initiatives. A knowledge-based and globalized society would not be possible without ICTs (Information and Communications Technologies). The 21st century workforce and the institutions that prepare them for it must adapt to as much change as there is in ICT itself. As a global phenomenon, ICT is posed as a major challenge and an opportunity for television education. As well as the issues and potential solutions to their effective integration in TVET, the chapter describes TVET's meaning, philosophy, objectives, types of ICT, and role in TVET.